Passive Capture and Ensuing Issues for a Personal Lifetime Store - Gemmell, Jim; Williams, Lyndsay; Wood, Ken; Lueder, Roger; Bell, Gordon (First ACM Workshop on Continuous Archival and Retrieval of Personal Experiences (CARPE '04), 2004)
Passive capture lets people record their experiences without having to operate recording equipment, and without even having to give recording conscious thought. The advantages are increased capture, and improved participation in the event itself. However, passive capture also presents many new challenges. One key challenge is how to deal with the increased volume of media for retrieval, browsing, and organizing. This paper describes the SenseCam device, which combines a camera with a number of sensors in a pendant worn around the neck. Data from SenseCam is uploaded into a MyLifeBits repository, where a number of features, but especially correlation and relationships, are used to manage the data.